The Effect of Ethanolic Extract of Moringa oleifera Leaves on the Macrophage Count and VEGF Expression on Wistar Rats with Burn Wound - Agnes Stella Valentina; Najatullah; Trilaksana Nugroho; Neni Susilaningsih (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: One modality type of burn wound therapy is topical silver sulfadiazine. Recently, research about topical herb medicine has grown. Moringa oleifera (MO) is a kind of herb plant that has an anti-inflammation effect and has an influence on angiogenesis, so it tends to faster burn wound healing. This study aimed to prove the effect of ethanolic extract of Moringa oleifera leaves on the macrophage count and VEGF expression in Wistar rats with burn wounds. Methods: The research design that was used is "Randomized post-test with a control group." The study population used 24 male Wistar rats that were induced burn wounds and randomly divided into 4 groups which were given medicine topically once daily for 7 days. Treatment groups included: I (MO leaves extract 10%), II (SSD + MO leaves extract 10%), III (SSD), dan IV (pure vehiculum). Exudation was assessed macroscopically, while PMN and macrophage amount were assessed microscopically with Hematoxylin-Eosin. Data were analyzed and processed using hypothesis test One Way ANOVA – Post Hoc Bonferroni, Kruskal Wallis – Mann Whitney, and correlation test Spearman and Pearson with SPSS 25.0 program. Results: Significant difference obtained in macrophage amount between II group and IV group (p 0,000). There was no significant difference in VEGF expression. There was also no correlation between macrophage amount and VEGF expression. Conclusion: Ethanolic extract of Moringa oleifera leaves extract proved to be effective in decreasing macrophage cell count on Wistar rats with burn wounds.